PENGEMBANGAN BAHAN AJAR TEORI ORGANISASI BERBASIS CONCEPT MAPPING TERHADAP KEMAMPUAN KRITIS - Siti Suprihatin; Heri Supranoto (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Teaching materials are a set of information that is presented in printed and non-printed forms which contain material as well as the constraints that must be understood by students through pleasant learning. This research is a study using research and development methods, better known as Research and Development. Research and Development Method is a research method used to produce certain products. Based on the results of the recapitulation on the value of validation of teaching materials based on Conceps Mapping obtained from validation 1 amounting to 65.00%, validator 2 at 68.00%, validator 3 at 66.00%, and validator 4 at 66.00% so based on result 4 the validator can be taken on average the value of validation of teaching materials based on Conceps Mapping is 66.25% and fulfills the criteria very well. The quality of the learning material obtained from several evaluations by the validators, namely material experts, language, design and critical thinking obtained results that the teaching material based on Conceps Mapping is quite feasible to use. Based on the conclusions that can be presented by the researcher that: 1) Feasibility of teaching materials based on Conceps Mapping from experts, namely: material experts on aspects of material feasibility obtained 84.42%, b) on language aspects obtained 81.33%, c) on design feasibility obtained 79.75%. d) and on the aspect of critical thinking students get 75.50%. The average value of the validation of teaching materials based on Conceps Mapping is 80.25% with a fairly decent category. 2) Student responses to the development of teaching materials based on Conceps Mapping in this organizational theory course from small groups and large groups, namely